A Historical-Philological Reassessment of Al-Arba'ūna fi Al-Tasawwuf and Its Contribution to Early Sufi Engagements with Hadith - Muhammad Royyan Faqih Azhary; Ahmad Firdaus; M. Hazim; Achmad Roziqi; Advan Navis Zubaidi (JURNAL AT-TURAS, 2025)
This study analyzes the epistemological intersection between Sufism and Hadith Science through an in-depth examination of the work of Abū ‘Abd al-Raḥmān al-Sulamī, al-Arbaʿūn fī al-Taṣawwuf. Using a historical-philological method, the research reveals the mechanism of the "methodological dialogue" initiated by al-Sulamī, which seeks to reconcile the authority of hadith transmission (naql) with the spiritual epistemology of Sufism (kashf). Empirical philological findings indicate that the majority of hadiths in this collection are of weak (ḍaʿīf) or even fabricated (mawḍūʿ) status, yet doctrinally, al-Sulamī strategically employs them to construct a Sufi ethical-spiritual foundation centered on the concepts of zuhud, maḥabbah, and maʿrifah. This study clearly distinguishes between the findings of problematic sanad authenticity and al-Sulamī's interpretative claims that validate hadith through the alignment of meaning (ṣiḥḥat al-maʿnā) and spiritual considerations. The resulting epistemological insight demonstrates that this work is not merely a harmonious reconciliation, but rather a negotiation arena reflecting the creative tension between the historical-textual authority of the muhaddithūn and the inner experiential authority of the Sufis within the medieval Islamic intellectual tradition.